The Interaction of Multi-Component Rare Earth Element-bearing Aqueous Solution with Ca-Mg-Fe-Carbonates and Fe-Phosphates under Hydrothermal Conditions - Maddin, Melanie (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2026)
This study aims to investigate the uptake and fractionation of rare earth elements (REEs) by divalent carbonates and Fe-phosphate minerals and to better understand the reaction pathways and crystallisation sequences that lead to the formation of REE-bearing minerals. Three main studies were conducted in which host grains (Mg-Ca carbonates, Fe-carbonate, and Fe-phosphate) were reacted with multi-component (La, Ce, Pr, Nd and Dy)- bearing aqueous solutions with varying REE ratios. Each experiment was a progression, with an increase in chemistry complexity, the introduction of redox reactions, crystallisation of nanophases and simultaneous, coupled reactions. This allowed for the study of more progressively dynamic reactions, such as solution mediated-dissolution and oxidation sequences as well as the formation of multiple REE, Fe, and P-bearing phases. Better insight into the intricacies of REE-mineral formation in the presence of foreign ions such as Fe and P in various environmental conditions could positively impact improved resource separation and recovery.
APPROVED
Keywords: cerianite; crystallization; hydroxylbastnasite; kozoite; rare-earth-carbonates